The Lincoln-Douglas debates : the first complete, unexpurgated text - Lincoln, Abraham, 1809-1865 (Fordham University Press, 2004)
"The seven debates between Abraham Lincoln and Stephen Douglas held during the Illinois senatorial race of 1858 are among the most important in American history. Classics of political rhetoric, the debates embodied dramatic struggles over the issues that would tear apart the nation in the Civil War: the virtues of a republic and the evils of slavery." "In this book, Harold Holzer brings us as close as possible to what Lincoln and Douglas actually said. He successfully confronts what has been a problem for historians: the accuracy of the transcriptions of the debates. The debates were transcribed by reporters of many newspapers, each unabashedly partisan. Historians have long been suspicious of the accuracy of many accounts since reporters often reported the debates through prejudiced lenses." "Holzer takes steps to ensure maximum fidelity to the words of Lincoln and Douglas. Using transcripts of Lincoln's speeches as recorded by the pro-Douglas newspaper, and vice versa, he offers the most reliable, unedited record available of the debates. He also includes detailed background on the two combatants, the sites, and on the often exuberant reactions and comments of the audience."--Jacket